Catalytic Properties for Decomposition of sec-Butyl Alcohol Over ZnO@SiO2 Nanocomposites Sol-Gel Catalysts - Zhu, Xiaomei; Li, Ru; Long Nguyen, Ngoc; Sun, Bing (Asian Journal of Chemistry, 2014)
ZnO/SiO2 catalysts of two different zinc oxide contents were prepared by the sol-gel technique and calcined at 653 and 953 K. ZnO/SiO2 catalyst with 9 % zinc oxide content was prepared by impregnation method as compare. The samples prepared were then used as catalyst in the decomposition of sec-butyl alcohol. They were found to give the opposite selectivity for dehydrogenation or dehydration on the catalysts prepared via the different methods. Characterization of the catalysts by TEM, BET and XPS confirmed that the difference of selectivity for dehydrogenation or dehydration was no obvious relation with the crystal, size, surface area, pore volume and reaction temperature. Further studies indicate that the reason of the different surface properties is caused by different interactions between zinc oxide and the silica matrix.